(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The relevance of this work is due to the high prevalence of allergic rhinitis (AR) and bronchial asthma (BA). AR affects 10% to 40% of the population, while BA affects an average of 5% to 10% of the population in various countries. Numerous epidemiological studies have demonstrated a close relationship between these conditions. Thus, 80-98% of patients with BA have AR, and up to 40-56% of patients with rhinitis have BA. It has been found that AR precedes BA in the majority of cases (32-64%) and is a risk factor for its development. AR is often underdiagnosed in clinical practice. The time from the onset of symptoms to diagnosis of AR is 4 to 8.5 years. In 2021, members of the WHO expert working group adopted the "Allergic Rhinitis and its Impact on Asthma" (ARIA) program, which identified the main challenges in the diagnosis and treatment of AR. The relationship between AR and asthma is the subject of intensive research. In recent years, three most likely mechanisms for this interaction have been identified: the shutdown of the physiological function of the nose, the rhinobronchial reflex, and the so-called "inflammatory" reflex. However, the condition of the lower respiratory tract in patients with AR without asthma remains poorly understood. Further research is needed to understand how AR and asthma influence each other’s course and patients’ quality of life.